Genomic and phenotypic profiling of an Artemisia endophyte: dual biostimulant and biocontrol activities in pea under Fusarium stress - Hadian, Shervin; Smith, Donald L.; Suproniene, Skaidre (Frontiers in Microbiology, 2025)
ObjectiveTo evaluate the plant growth-promoting and disease-suppressing potential of Serratia sp. AR11, an endophytic bacterium isolated from Artemisia absinthium, through phenotypic assessment and whole-genome analysis in pea (Pisum sativum) under normal and Fusarium-stress conditions.Materials and methodsGreenhouse experiments were conducted to assess the effects of AR11 inoculation on shoot and root growth, biomass, chlorophyll content, and Fusarium-induced stunting. Whole-genome sequencing was performed using the PacBio SMRT platform, followed by functional annotation to identify genes related to nutrient metabolism, secondary metabolite biosynthesis, and stress adaptation. Biosafety assessment included screening for virulence and antibiotic resistance genes.ResultsAR11 inoculation significantly increased shoot and root length and biomass, while reducing Fusarium-induced stunting by over 70%. Under pathogen stress, treated plants showed a 67% increase in SPAD index compared to controls. Genome analysis revealed a complete 5.49 Mb circular genome with 5,175 protein-coding genes, including those for nitrogen metabolism, phosphate solubilization, siderophore production, and antifungal secondary metabolite biosynthesis. Additional features included stress-responsive regulatory systems, CRISPR-Cas loci, and DNA methylation patterns. No high-risk virulence or acquired antibiotic resistance genes were detected.ConclusionSerratia sp. AR11 is a safe, multifunctional endophytic bacterium with strong genomic and phenotypic evidence for enhancing pea growth and suppressing Fusarium-related diseases, making it a promising candidate for sustainable low-input agriculture.